ANALISIS PENGARUH KUALITAS VIDEO ROLLING TERHADAP KINERJA STASIUN RELAY TRANS7 PONTIANAK - ., Fajar Maulana (Jurnal Teknik Elektro Universitas Tanjungpura, 2013)
Abstract Video Rolling is caused by the exciter which is the generator of audio signal as well as video signal which is produced from the receiver unit, that is a part of the internal disturbance. Video Rolling happens because of the unsyncrhonization between the audio signal and the video signal. The unsyncrhonization is caused by the audio signal is faster than the video signal, so that the place of sound information surpass the destination of video information and the video signal is faster than audio signal, so that the place of picture surpass the data information which is given. This video rolling happens because of the unsyncrhonization between audio signal and video signal which comes from exciter to other wares to supply information. From so many disturbances which have happened in Trans7 Pontianak Relay Station, video rolling is the disturbance which happens rarely but it needs the long handling in order to make the broadcasting process back to run normal. Keywords : Video rolling, audio signal, video signal.